Giant Desmoid Tumor in the Pelvis: A Case Report - Davut Güven; İsmail Kılıco; Yıldırım Durak; İdris Koçak; Cazip Üstün; Oğuz Aydın (Medical Network, 2009)
A 30 years old patient presented with complaint of abdominal discomfort and distension. The patient was gravida 1 and para 1. Ultrasonographic examination revealed a 90x83 mm sized mixed echoic pelvic mass located at the posterior of uterus. With an exception of high CA125 level of 63 IU/ml (cut-off is 35), the other serum laboratory findings were in normal ranges. She had not any history of familial or chronic diseases and she had a C-section six years ago. A laparotomy was performed and uterus, bilateral tuba uterina and ovaries observed as normal. A 20x25 mm sized, creamy coffee colored, solid natured, lobulated, hard mass was located at the paraumbilical region, bound to anterior abdominal via a thin pedicle.